Active Surveillance of Papillary Thyroid Microcarcinoma: Where Do We Stand? - Jeon, Min Ji (Eur Thyroid J, 2019)
The recent sharp increase in thyroid cancer incidence is mainly due to increased detection of small papillary thyroid microcarcinoma (PTMC). Due to the indolent nature of the disease, active surveillance (AS) of low-risk PTMCs is suggested as an alternative to immediate surgery to reduce morbidity from surgery. For appropriately selected PTMC patients, AS can be a good management option and surgical intervention can be safely delayed until progression occurs. Many considerations must be taken into account at the time of initiation of AS, including radiological tumor characteristics and clinical characteristics of the patient. A specialized medical team should be assembled to monitor patients during AS with an appropriate follow-up protocol. The fact that some patients require surgery for disease progression after long-term follow-up is a major drawback of the current AS protocol. Evaluation of tumor kinetics by three-dimensional tumor volume measurement during the initial 2–3 years of AS may be helpful for discrimination of PTMCs that need early surgical intervention. In this review, we will discuss the clinical outcomes of surgical intervention and AS, considerations during AS, and unresolved questions about AS.